Merging actors with events: introducing the social conflict analysis dataset – organizational properties (SCAD-OPs). Issue 1 (2nd January 2020) - Salehyan, Idean; Feinberg, Ayal
ABSTRACT: Events data have been instrumental in the study of contentious politics. Yet such data often focus on the attributes of the events themselves – such as the number of participants, fatalities, and location – while providing scant information on those involved. To address this shortcoming, we introduce the Social Conflict Analysis Database – Organizational Properties (SCAD-OPs). This dataset categorizes the organizations and identity groups involved in the original SCAD, which allows analysts to answer important questions about who is involved in social conflict. Named entities are assigned to seventeen domains, or primary functional areas, including government, labor, criminal, activist, and so on. Individuals and groups that have a coherent identity – enabling researchers to track their activities over time – are assigned unique organizational codes, and factions within organizations are also identified. Presenting data from seven countries, we provide descriptive statistics on the types of entities most likely to be principal SCAD actors and targets across countries, as well as a preliminary analysis, linking participants with event types. We assess which domains are most likely to engage in peaceful protests, violent riots, strikes, and armed attacks. Finally, we discuss potential questions that can be addressed using this data.